Compensation, Work Environment, and Employee Performance: The Mediating Role of Work Motivation at the Cultural Preservation Center of North Maluku Province - M.Rizky Ramadhan; Muhammad Thahrim; Muhammad Asril Arilaha (International Journal of Business, Law, and Education, 2026)
This study examines whether work motivation mediates the relationships between compensation, work environment, and employee performance at the Cultural Preservation Center (Balai Pelestarian Kebudayaan [BPK]) of North Maluku Province. A quantitative cross-sectional census survey was administered to all 50 active civil servants, comprising both permanent civil servants (PNS) and government employees with work agreements (PPPK). Data were collected using a five-point Likert-scale questionnaire and analyzed through partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4. Compensation was positively associated with work motivation (β = 0.583, p < 0.001) but had no significant direct association with employee performance (β = -0.018, p = 0.455). The work environment was positively associated with employee performance (β = 0.424, p = 0.001) but not with work motivation (β = -0.024, p = 0.431). Work motivation was positively associated with employee performance (β = 0.472, p < 0.001). Moreover, work motivation significantly mediated the compensation-performance relationship (indirect effect β = 0.275, p = 0.002), whereas it did not mediate the work environment-performance relationship (β = -0.012, p = 0.433). These findings indicate that compensation and the work environment contribute to performance through distinct motivational and operational pathways.